ANALISIS PENERAPAN MANAJEMEN DAN STRATEGI DISTRIBUSI BERAS DI PERUSAHAAN UMUM BADAN URUSAN LOGISTIK (PERUM BULOG SUB DIVRE KOTA GORONTALO) - Tangkudung, Anggun Juwita; Halid, Amir; Saleh, Yanti (Agrinesia: Jurnal Ilmiah Agribisnis, 2016)
This study aims to determine how the application management and Perum Bulog's role in the distribution of rice, and to determine the factors and what strategies are dominant in the development of rice distribution in Gorontalo city Divre Perum Bulog. This research conducted in June-July 2016. The analysis method used in this research is descriptive method of management and SWOT analysis. Sampling was done by the method or approach the case with staff Perum Bulog sub Divre city of Gorontalo. These results indicate that the Application Management and Role Bulog: (1) Planning, namely planning and scheduling pendistrbusian rice, determine when the distribution is done and the time of distribution (2) The organization is using labor, distribution system, and the means of transport (3) Implementation of that packaging or the current form of distribution, news of the handover ceremony and was preparing to needs (4) Evaluation namely distribution planning activities, targeted distribution, organization during the distribution, implementation of activities and constraints for distribution. the SWOT Matrix, the factors and strategies for developing the distribution of rice, namely (1) Utilizing a network of government for the distribution of poor rice in each village so that every distribution could run well (2) With the checking of the preparation to face the threat could be in Who are the early and ( 3) With an award then Bulog can provide confidence when socializing to each village. the weakness of the factors and strategies for developing the distribution of rice (1) To Ful Fil for cooperation with other partners in order that the distribution of poor rice could run well (2) it needs the network to perispan to face a problem in the distribution of it can be done and (3) need any interference from the government to socialization of each village to be going well. Keywords: Application Management, Distribution Strategy, Rice, Perum Bulog